Efficient biosynthesis of D/L-alanine in the recombinant Escherichia coli BL21(DE3) by biobrick approach - Naeem, Muhammad; Hao, Shimiao; Chu, Mengqiu; Zhang, Xuan; Huang, Xinyan; Wang, Jiaying; He, Guangzheng; Zhao, Baohua; Ju, Jiansong (Frontiers in Bioengineering and Biotechnology, 2024)
Alanine is the most abundant chiral amino acid that exists into the D-alanine or L-alanine forms with diverse applications in the biomedical, pharmaceutical, plastics, and food industries. D/L-alanine production can be carried out through chemical, microbial fermentation, and biocatalytic methods and not much effective due to complicated processes or purification issues and is still challenging to achieve a higher yield. In the present study, biobrick method was utilized for efficient production of D/L-alanine in the recombinant Escherichia coli BL21(DE3) with tandem three-gene co-expression plasmid. Firstly, the co-expression plasmid pET-22bNS-DadX-Ald-Gdh containing three genes, alanine dehydrogenase (ald), alanine racemase (dadx), and glucose dehydrogenase (gdh) from Bacillus pseudofirmus OF4 were successfully constructed and introduced into the E. coli BL21(DE3) strain. Then, under optimized conditions in the whole-cell biocatalytic reaction [20 mM Na2CO3-NaHCO3 (pH 10.1), 200 mM D-glucose, 200 mM sodium pyruvate, and 200 mM ammonium chloride), the concentration of D-alanine and L-alanine reached the maximum value (6.48 g/L and 7.05 g/L) after 3.0 h reaction time at 37 °C under 180 rpm rotation. Meanwhile, promoter replacement experiments and western blot analysis revealed that the expression level of protein OF4Ald had a significant effect on the production of D/L-alanine, indicating that alanine dehydrogenase might be the rate-limiting enzyme for D/L-alanine synthesis. This study provides a simple, feasible, and efficient biosynthesis process of D/L-alanine, which could explore emerging applications for large-scale production of industrial bioproducts.